American Bison Impacts on Riparian and Wallow Vegetation Communities - Yu, Sze Wing (Clemson University Libraries, 2021)
Grasslands are one of the most threatened landscapes in North America, and the Northern Great Plains Ecoregion of Montana has been identified as a global priority for grassland conservation. Within this ecoregion, the nonprofit American Prairie Reserve was created to establish a large conservation herd of plains bison (Bison bison bison, hereafter referred to as bison) in an effort to restore the landscape to ecological conditions prior to agriculture in the region. Bison are regarded as a keystone species for their unique behaviors that drastically influence ecosystem structure and function. Among these behaviors is a decreased use of riparian zones compared to cattle, which may lead to the recovery of riparian vegetation communities from overgrazing and trampling. Bison also create patches of disturbed soils on the landscape called wallows, which may provide habitat to plant species that would otherwise be outcompeted on the surrounding prairie, thus increasing landscape plant biodiversity. The Northern Great Plains is experiencing controversy over the bison restoration due to local concerns that year-round bison grazing will negatively impact riparian areas and upland forage more than seasonal cattle grazing, which is the norm. The objective of our first chapter was to compare the riparian vegetation community response to year-round bison grazing versus seasonal cattle grazing. In 2019 and 2020 we surveyed vegetation and soil compaction within riparian zones of pastures exposed to either seasonal cattle grazing or year-round bison grazing. Out of 24 vegetation and soil variables we measured, we found that native species richness and woody height heterogeneity were higher in the bison restored sites than the cattle-grazed sites, while the rest of the variables did not differ between grazer treatments. Collectively, our findings show that bison restoration may be beneficial for some aspects of the riparian zone, and support reviews critiquing the promotion of seasonal grazing as superior to year-round grazing ...